Making sense of complex numbers - Elvent Taliban (2019)
This research exemplifies a framework of mathematical thinking as proposed by Chin & Tall (2012) and Chin (2013) by showing the empirical evidence related to how a group of participants made sense of complex numbers. Humans make sense of new mathematics context by relating it to personal conceptions and experiences. This might not be a smooth process as it may involve conceptions that work in an old context but do not work in a new context. The researcher has chosen the topic of complex numbers as it is an extension of the real numbers system and it will be beneficial to explore how the conceptions of participants in the real numbers system affect their sense making of complex numbers. This study involves thirty undergraduate students majoring in mathematics from the faculty of Science and Natural Resources, Universiti Malaysia Sabah. After analysing the responses of the participants for the given mathematical task, a follow-up interview was conducted with five participants. The interview session was recorded and transcript were made of the interviews. The transcripts were then analysed. The results show that these participants have supportive and problematic conceptions in making sense of complex numbers and these conceptions are originated from the context of real numbers.